1997
DOI: 10.1159/000262390
|View full text |Cite
|
Sign up to set email alerts
|

Flow Rate and Composition of Whole Saliva in Children from Rural and Urban Thailand with Different Caries Prevalence and Dietary Intake

Abstract: The aim of this study was to compare the prevalence of dental caries, dietary composition and whole salivary flow rates together with some of the components of saliva between two groups of children aged 12-16 years, one group from an urban area and the other from a rural area of Thailand. A stratified random samples were taken by class from one schools in each area. The children who had mixed dentition and/or who had migrated from other area of Bangkok and 138 students were selected from a school in a rural ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 8 publications
1
22
1
6
Order By: Relevance
“…The group IV had lowest buffering capacity and higher values of DMFT concluding that buffering capacity had a strong correlation with dental caries. The study conducted by Johansson I et al and Saelbtröm A-K et al 21 , showed that, the decreased buffering capacity due to more acidic pH, resulted increased incidence of dental caries, which supports the present study. Also the study conducted by WG Young et al states that the decreased buffering capacity causes the demineralisation of the tooth structure which results in dental caries, which supports our present study.…”
Section: Discussionsupporting
confidence: 89%
“…The group IV had lowest buffering capacity and higher values of DMFT concluding that buffering capacity had a strong correlation with dental caries. The study conducted by Johansson I et al and Saelbtröm A-K et al 21 , showed that, the decreased buffering capacity due to more acidic pH, resulted increased incidence of dental caries, which supports the present study. Also the study conducted by WG Young et al states that the decreased buffering capacity causes the demineralisation of the tooth structure which results in dental caries, which supports our present study.…”
Section: Discussionsupporting
confidence: 89%
“…This unstimulated flow, is what is secreted by the salivary glands the majority of the time. Unstimulated saliva is essential for the health and well being of the oral cavity and also bestows a strong protective effect to the oral cavity, against dental caries [10].…”
Section: Resultsmentioning
confidence: 99%
“…16 mostraron asociación entre altas concentraciones de calcio y fosfato en saliva total y baja prevalencia de caries en niños residentes en áreas rurales. Por el contrario, Kargul et al 15 no detectaron diferencias en la composición inorgánica de la saliva entre niños que presentaban o no caries.…”
Section: Discussionunclassified